REPRESENTASI FAKTA-FAKTA SOSIAL-POLITIK DALAM NOVEL AMBA KARYA LAKSMI PAMUNTJAK - Yuantisya, Mutia; Nurizzati, Nurizzati; Nst., Bakhtaruddin (Jurnal Bahasa dan Sastra, 2018)
The purposes this study were to (1) describtion about authority domination representation in Amba’s novel by Laksmi Pamuntjak, (2) describtion about inter-class conscious conflict in Amba’s novel by Laksmi Pamuntjak, (3) describtion about inter-class religion conflict in Amba’s novel by Laksmi Pamuntjak, and (4) describtion about force representation in Amba’s novel by Laksmi Pamuntjak. Data in this study are word, phrase, clause, sentence, and paragraph to be contact with social-political facts representation in Amba’s novel by Laksmi Pamuntjak. The primary source of data is Amba’s novel by Laksmi Pamuntjak from Gramedia Pustaka Utama publisher on 2015. Data were collected by (1) reading and understanding of Amba’s novel by Laksmi Pamuntjak with remark in part story as data, and (2) data inventory by using format. The findings this study are authority domination representation, inter-class conscious conflict, inter-class religion, and (4) force representation in Amba’s novel by Laksmi Pamuntjak.Keywords: representation, social-politic facts